Antimicrobial Intervention by Photoirradiation of Grape Pomace Extracts via Hydroxyl Radical Generation - Niwano, Yoshimi; Tada, Mika; Tsukada, Mana (Frontiers in Physiology, 2017)
The annual production of grape worldwide amounts to almost 70 million tons, and around 80% is used for winemaking. The two major wastes from winemaking process, pomace and lees account for 20% and 7% of the grapes, respectively. They have been expected as a valuable resource to be recycled because they are rich in polyphenols. Polyphenols possess prooxidatve activity as well as antioxidative one just like a two sides of a coin. A typical example of the prooxidative activity is antibacterial activity of catechins. The activity is exerted through oxidation of phenolic hydroxyl moiety coulpled with reduction of dissolved oxygen leading to hydrogen peroxide (H2O2) generation. In addition, once the oxidation of phenolic hydroxyl moiety is augmented by photoirradiation, highly reactive hydroxyl radical (·OH) is generated. Accordingly, there have been several reports showing that photoirardiation of polyphenols exerts bactericidal activity via ·OH generation. This review focuses mainly on antimicrobial intervention by photoirradiation of grape pomace extract in relation to ·OH generation analyzed by an electron spin resonance-spin trapping method.